Isolation and gene expression profiling of drought-responsive genes in upland rice (Oryza sativa L.) - Lum, Mok Sam (2016)
Abiotic stresses negatively affect stable crop production yield world-wide. The yield of rice production is affected by drought or water deficit. Water shortage and uneven rainfall distribution limit the use of available water for rice production. The irrigation costs increase yearly in water limited area. Therefore, developing rice varieties with high water use efficient is needed currently. Upland rice performs better and drought tolerant under water limited environment although the yield is low. Therefore, the upland rice can serve as genetic resources for genetic manipulation of susceptible crops. The objectives of the study were: (i) to screen for drought-tolerant upland rice varieties, (ii) to isolate and identify the expressed drought-responsive genes in drought-tolerant upland rice under water limitation, and (iii) to examine the differential expression of transcripts under drought stress and normal conditions. Investigation was performed to evaluate 38 upland rice varieties with five drought levels at germination and early seedling growth stage using PEG 6000 as drought inducer. Drought tolerant variety, IR5533-15-1-1 (S24) had better germination indices, root length, the highest enzymatic antioxidant activity and non-enzymatic antioxidant level (proline) compared to sensitive varieties. Pot experiment was conducted on IR5533-15-1-1 (S24) variety that were (i) watered regularly (un-treated and control plants) and (ii) treated with PEG 6000 solution (-8 bar) for five days at reproductive stage. Then, isolated mRNA from leaves (control and treated plants) was used to generate subtracted cDNA library. The expressed sequence tags (ESTs) were analyzed. Reverse transcriptase PCR and real-time PCR were conducted to analyze the expression profiles of drought-responsive genes from upland rice. Two EST sequences identified showed 87% and 97% similarities to that of glutathione Stransferase (GST) and dehydrin (DHN) from rice, respectively. The expression levels of GST and DHN transcripts in PEG-treated plants were higher than those of untreated plants. The expression of GST was up-regulated and reached a peak at 3 days after treatment (DAT) in leaves (2.5 folds increase) and roots (2 folds increase). On the other hand, the levels of DHN expression showed higher expression in leaves and roots at 4 DAT (2.1 folds increase) and 3 DAT (2.7 folds increase), respectively. The up-regulation of GST and DHN transcripts indicate upland rice defense response was activated during drought stress. This study has successfully identified the differentially expressed drought-responsive genes in upland rice under drought stress.